Analysis Behavior Education Personnel Administration In Utilization E-Office As Embodiment Paperless Offices - Brillian Rosy; Cipto Wardoyo; Heri Pratikto; Madziatul Churiyah; Vindi Kusuma Wardani (Cita Konsultindo Research Center, 2023)
The purpose of this research is to find out and analyze the administrative behavior of educational staff using an e-office as a paperless office at the Faculty of Economics and Business, Surabaya State University. This research uses a quantitative descriptive research approach. This research method is survey research. The population in this research is the educational staff of the Faculty of Economics and Business, Unesa. The results showed that of the three factors as a whole, the Enabling Factor (supporting factor) had the highest contribution (41%) in the administrative behavior of educational staff in the use of e-office as a form of paperless office at the Unesa Faculty of Economics and Business. Effective and efficient administrative behavior will affect the dynamics of the organization in realizing the goals that have been set before. Educational staff is one of the actors (administrative staff) in the administrative work of an educational institution. So the urgency of this research is to find out how the administrative behavior of the educational staff is in the use of e-office as a form of paperless office at the Faculty of Economics and Business, Surabaya State University.